SPE Annual Technical Conference and Exhibition 2013
DOI: 10.2118/166402-ms
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Fluid Mobility in Fractured Cores Using Time-lapse Positron Emission Tomography

Abstract: Positron emission tomography (PET) continues to have wide-ranging medical application and is based on the detection of gamma radiation emitted from the decay of certain types of radionuclides. Modern PET scanners produce three-dimensional (3D) images of the radiation source, in discrete time steps, using tomography analysis. This paper presents an application of PET for studying fluid mobility in pressurized low-permeability rock samples in the presence of natural fractures. This technique uses a high-resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A 3D image can be constructed from a collection of such LORs, measured at many angles, using tomography analysis. Further details on the PET method are presented by Maučec et al (2013aMaučec et al ( , 2013bMaučec et al ( , 2013c and in references therein (e.g., Saha 2010).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A 3D image can be constructed from a collection of such LORs, measured at many angles, using tomography analysis. Further details on the PET method are presented by Maučec et al (2013aMaučec et al ( , 2013bMaučec et al ( , 2013c and in references therein (e.g., Saha 2010).…”
Section: Methodsmentioning
confidence: 99%
“…This approach (Maučec 2013b) uses and benefits from a new method and algorithm for the analysis of list mode data from PET experiments, which efficiently achieves the maximum possible spatial resolution (Bickell et al 2012). Traditional PET imaging techniques typically rely on static or quasi-static systems.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number, position and size of PET detector elements, as well as the distance between the object and detectors, strongly influence the spatial resolution of PET imaging [1]. PET is established as a diagnostic tool in medicine, where the radioactively labelled "object" is often a human (in clinical imaging) or animal (in pre-clinical research) but has also recently been demonstrated as a highly useful tool for non-medical purposes: flow visualization in porous rocks [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. For practical purposes the beta plus decay is insensitive to pressure and temperature [16].…”
Section: Background 1a Quick Introduction To Positron Emission Tomogr...mentioning
confidence: 99%